GAMBARAN CEDERA KEPALA PADA KORBAN KECELAKAAN LALU LINTAS DI BAGIAN BEDAH RSUP DR. M.DJAMIL PADANG TAHUN 2019-2020 - Insil Pendri Hariyani; Puji Rizki Rasyid; Dian Ayu Hamama Pitra (Nusantara Hasana Journal, 2023)
One type of trauma experienced by motorized vehicle drivers that can be fatal to bodily functions that can lead to death is a head injury. RSUP Dr. M. Djamil Padang is a referral center hospital in the province of West Sumatra so by looking at patients with head injuries due to traffic accidents who enter the hospital, it will represent a picture of traffic accident victims who suffer head injuries in West Sumatra. This research is a categorical descriptive study which was carried out in August - September 2021 by looking at the medical record data of patients treated at the Surgery Department of RSUP Dr. M. Djamil Padang in 2019-2020 and obtained 70 samples of patient medical records using a purposive sampling technique. Univariate data analysis was presented in the form of a frequency distribution and data processing using the computerized SPSS program IBM version 25.0. This study shows that in cases of head injuries due to traffic accidents it was found that most of the victims were male, in their late teens, not working, with accompanying diseases of lower extremity fractures, the classification of head injuries was moderate injury, the location of the head injury was in the temporalis many abrasions and Intracerebral Haemorrhage (ICH) were found.